EFFECTIVENESS IN IMPLEMENTING SUPREME COURT REGULATION OF THE REPUBLIC OF INDONESIA NUMBER 2 YEAR 2015 ON PROCEDURES SETTLEMENT OF SIMPLE LAWSUIT IN SETTLING THE CIVIL CASES - Wiryatmo Lukito Totok; Anik Iftitah (Universitas Islam Balitar, 2017)
President Regulation of the Republic of Indonesia Number 2 Year 2015 on the National Medium Term Development Plan 2015-2019 mandates to carry out Reformation of the Civil Code system which is easy and fast, in an effort to improve the competitiveness of national economy. Related to this, the Supreme Court answered the vacancy of a simple lawsuit by issuing Regulation of the Supreme Court of the Republic of Indonesia (PERMA) Number 2 Year 2015 on procedures for settlement of simple suit in settling civil cases. The empirical juridical research in the Court of Kediri showed that the implementation of Regulation of the Supreme Court of the Republic of Indonesia Number 2 Year 2015 made the lawsuit procedure simpler and very effective and in accordance with the principle of simple, fast and light cost. Effectiveness Index of Regulation of the Supreme Court of the Republic of Indonesia Number 2 year 2015 at Kediri District Court Class I B was in the